Computational simulation of the fluid flow in a subsonic jet-pump (2024)
ABSTRACT : This study aims to develop the computational elements necessary to predict through CFD simulations, the performance of a subsonic jet pump operating with water, focusing on the pressure ratio, flow ratio, energetic efficiency, and the internal flow field. The RANS-based turbulence models k-ω SST and k-ε, along with standard, scalable, and enhanced wall functions are used to simulate the behavior under eight different flow ratios for three different nozzle spacings. These geometries, discretized using well-structured meshes, are reviewed in terms of mesh quality and mesh independence through a sensitivity analysis and the comparison with the theoretical boundary layer. The results are compared with each other and with experimental data available in the literature to validate the implemented simulation environment and determine which models best captures each aspect of the performance. Numerical analysis shows that the simulations accurately predict the phenomena governing the jet-pumps, where the average relative error in efficiency for k-ε is 7.3% and for k-ω SST is 8.47%, analogously, for the pressure coefficient that accounts for the device pumping it is 10.68% and 3.21% respectively. Additionally, the velocity and pressure contours prove that at lower flow ratios there is a higher pressure ratio between the outlet and the inlets, and as the mixing zone approaches the end of the throat without exceeding it, as a result of an increased flow ratio, the efficiency reaches its maximum, as observed in previous research.